Industrial training report: Wistron Technology (Malaysia) Sdn Bhd / Anis Sofiya Baharin - Baharin, Anis Sofiya (Universiti Teknologi MARA, Perlis, 2024)
The internship was carried out in Port Klang at Wistron Technology (Malaysia) Sdn bhd. The internship ran for 24 weeks, starting on 1st March and ending on 9th August. Under the supervision of Mr David Lee, I have been assigned to the Learning and Development Department under Human Resource Management.Enhancing team members’ knowledge, ability and competences in a variety fields is the aim of our department. During my 24-week internship at Wistron Technology (Malaysia) Sdn Bhd, I oversaw a variety of human resource task to being involve in learning and development process, industrial relation process and recruitment process. Along with supporting several events such as Hari Raya Aidilfitri, I also collaborated closely with team members. Overall, my internship experience at Wistron Technology (Malaysia) Sdn Bhd provided a tremendous platform for personal and professional growth. Engaging projects and tasks have taught me so much, especially when it comes to actively participating in various section of Human Resource. In addidtion, to strengthening my academic knowledge, my internship experience have piqued my interest in the workplace and strengthened my will to seek a profession.